Impacts resulting from a possible rupture of a mining dam in the Municipality of Itabira, Minas Gerais State, Brazil (Research, Society and Development, 2020)
This work aimed to spatialize the flood spot and the impacts resulting from a possible rupture of the Pontal dam in the municipality of Itabira/MG. The data used were provided by the Municipal Civil Defense of the Municipal Department of Environment of the municipality. The methodology consisted of making maps with the spatialization of the floodplain and land use and occupation, using ArcGIS 10.3 software. In the event of the dam rupture, the main water body of the municipality, the Peixe River, which is downstream of the Pontal dam, in addition to its tributaries, would be affected. Consequently, there would be an impact on water quality, such as increased turbidity, reduced OD, and increased concentration of heavy metals and other elements present in mining tailings. There would also be impacts on the urban area, such as the destruction of homes, vegetation and fauna, in addition to the loss of human lives, if there is not rapid evacuation. The length of the stain is approximately 9.80 km in Itabira, but it exceeds the limits of the municipality. It is concluded that in the face of a possible rupture of the dam, the environmental damage downstream of the dam would be great, both for the municipality of Itabira, as well as for the other municipalities that could be affected, with the change in water quality, the devastation of vegetation and urban construction, in addition to the various forms of life present in the area.